Analisis Analisis Pada Aplikasi Simulasi Pergudangan Berbasis Virtual Reality Menggunakan Metode Game User Experience Satisfaction Scale (Guess) - yosua millyandi hutagalung; Riwinoto Riwinoto (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2022)
In the world of simulation, there are many issues related to how to make a simulation interesting and make users want to use it again. One of them is user satisfaction. User satisfaction is the extent to which players feel satisfied when using an application. The warehouse simulation application is an application that is based on three dimensions and can only be run using virtual reality technology. This application aims to simulate how the activities of a picker in the warehouse. This research was conducted to determine the level of user satisfaction when using the warehouse simulation application. The research was conducted using the Game User Experience Satisfaction Scale (GUESS) method which has nine subscales, namely usability, narratives, play engrossment, enjoyment, creative freedom, audio aesthetics, personal gratification, social connectivity, and visual aesthetics. Data collection was carried out by distributing questionnaires through online media. Respondents in this study were 30 students of the Batam State Polytechnic International Trade Logistics study program. The analysis method uses a descriptive quantitative method. The results of the analysis show that of the nine subscales of user satisfaction with the Warehouse simulation application, four subscales are below average, namely enjoyment, audio aesthetics, personal gratification, and social connectivity. From these results, what needs to be improved is the addition of audio and UI that gives appreciation to users to increase personal gratification, changing the color concept in each scene so that users do not feel bored with the application.